Analisis Pengaruh Sudut Kemiringan Terhadap Efisiensi Energi pada Sistem Pembangkit Listrik Tenaga Surya Menggunakan System Advisor Model Software - Muhammad Irsan; Nurul Chairunnisa Noor; Rhamadhana Sultan (Universitas Al Azhar Indonesia, 2026)
With an emphasis on Indonesia's solar energy potential, this study investigates how panel tilt angle affects energy efficiency in solar power-producing systems. Economic expansion is increasing the energy demand, which is driving a search for affordable, sustainable, and ecologically friendly renewable energy sources. Because solar power plants use sunlight to generate energy, it is crucial to design systems considering variations in sunshine intensity brought on by elements such as solar panel tilt angle. This experiment shows that adjusting the tilt angle can maximize solar energy absorption and increase conversion efficiency. By collecting meteorological data from a representative site in Makassar and conducting experiments with tilt degrees ranging from 0° to 60°, a dogmatic approach was taken. According to the results, an ideal tilt angle of 10° produces the most energy output each year, however angles between 30° and 40° work best from May to August when sunlight is at its strongest. The results show that to optimize solar energy efficiency and encourage the use of renewable energy, tilt angle modifications must be made appropriately based on seasonal variations.Keywords – Efficiency, Renewable Energy, Solar Power, Tilt Angle.